Influence of Curing Conditions on Strength Characteristics of Sea Sand Mortar - Datu, Irka Tangke; Ali, Adiwijaya; Jalali, Nur Aisyah; Khairil, Khairil (Politeknik Negeri Ujung Pandang, 2020)
This present paper aims to investigate strength characteristics of cement mortar using natural sea sand as fine aggregate in different curing conditions. Research was carried out with making mortar mixtures by two types of cement, Portland Composite Cement (PCC) and Pozzolana Portland Cement (PPC) with tap water as mixing water. Characteristics of fine aggregate and strength of cement mortar use river sand (RS), sea sand (SS), and washed sea sand (WS) were observed. Further, specimens of cube mortar in size of 50 mm x 50 mm x 50 mm of six mortar mixture series were casted according to Indonesian Standard. At 24 hours after cube specimens were casted, cube mortar specimens were cured in three curing conditions such as tap water curing (TC), seawater curing (SC) and air curing (AC). After curing at certain period (3-day, 7-day, 14-day, and 28-day), cube mortar samples were tested in compressive strength. Results concluded that sea sand aggregate improve characteristic of mortar in compressive strength up to 28 days in all curing conditions, and there was no significant effect of type of curing water (TC and SC) on 28-day strength performance of mortar was obtained. In addition, sea sand could potentially be utilized as an aggregate in production of mortar and/or concrete.